SUN-642 Paracetamol May Increase Cardiac Congenital Malformations Risk in Prediabetic Pregnancy Women - Guerrero, Juan Ariel Jara (J Endocr Soc, 2020)
ABSTRACT Hyperglycemia can influence the development of the fetal heart, affecting both its structure and its function. Prospective and retrospective cohort studies have demonstrated an increased risk of congenital abnormalities with gestational diabetes. This observation is probably related to the inclusion of women with unrecognized type 2 diabetes (Allen, 2007, Pasarella, 2013). Substantial literature indicates that diabetes in pregnant rats and mice induces embryo lethality, growth retardation, and a variable incidence of birth defects. Then, the maintenance of normal concentrations of metabolites from all nutrient classes may be important for prevention of adverse fetal outcome in diabetic pregnancy. Acetaminophen overdose is the most often cause of acute liver injury and obese women are in particular risk, because is able to induce mitochondrial oxidative stress (Rousar, 2012). Acetaminophen (Paracetamol) over doses decreased embryonic low-molecular-weight thiols (glutathione and cysteine), compounds that play a vital role in the detoxication of exogenous and endogenous chemicals (Mitchell, 1973, Beck, 2001, Rousar, 2012, rev). The apparent safety of Paracetamol drug, a useful analgesic only (with no anti-inflammatory properties) (Neto, 2004; Hamlyn, 1978, Ucheya, 2006, Bessems, 2001) is compromized by its widespread and extensive chronic use, particularly in Peruvian population- Paracetamol though considered safe at a considerable low dose, especially in women, could cause kidney derangement and cardiac malformations during pregnant state (Ucheya, 2006), if the drug is ingested in the first trimester. Major congenital malformations, including those affecting the cardiovascular system, remain the leading cause of mortality and morbidity in infants of diabetic mothers (Pinter, 2001). Thus, there is an overcome potential maternal acetaminophen (paracetamol) toxicity (Horowitz, 1997).